The Association between Transcatheter Aortic Valve Replacement (TAVR) Approach and New-Onset Bundle Branch Blocks - Ali M. Agha (Cardiology and Therapy, 2019)
Abstract Introduction Transcatheter aortic valve replacement (TAVR) has become a widely accepted treatment option for patients with severe aortic stenosis (AS) who are considered intermediate- and high-risk surgical candidates. The purpose of this study was to test the hypothesis that trans-apical TAVR would be associated with increased risk of new-onset intraventricular conduction delay (LBBB or RBBB). Methods We conducted a retrospective observational study of consecutive patients undergoing TAVR at a large, single institution. The incidence of new LBBB or RBBB was compared between femoral and apical TAVR patients. Multivariate analysis was performed to account for confounding variables, which included age, gender, CAD, PAD, hypertension, and diabetes. Results A total of 467 TAVR patients were included in the study, with 283 (60.6%) femoral approach and 184 (39.4%) apical approach. In univariate analysis, the apical approach (when compared to the femoral approach) was associated with a higher incidence of both new-onset LBBB (12.79 vs. 3.40%, p = 0.0002) and RBBB (5.49 vs. 0.81%, p = 0.0039). After controlling for potential confounding variables, the apical approach continued to be associated with a higher incidence of both new-onset LBBB (p = 0.0010) and RBBB (p = 0.0115). There was also a trend towards an association between diabetes and new-onset LBBB (p = 0.0513) in apical TAVR patients. In subgroup analysis, LBBB/RBBB occurring as a result of transapical TAVR was associated with more frequent hospitalizations > 30 days after TAVR, compared to transfemoral TAVR. Other post-procedural complications noted more frequently among patients undergoing transapical TAVR include arrhythmias including atrial fibrillation, peri-procedural myocardial infarction (within 72 h), mortality from unknown cause, and mortality from non-cardiac cause. Conclusions Relative to transfemoral TAVR, patients undergoing transapical TAVR are at increased risk for new-onset bundle branch block, peri-procedural myocardial infarction, rehospitalization, TAV-in-TAV deployment, and all-cause mortality at 1 year. Interventional cardiologists and cardiothoracic surgeons alike should take these findings into consideration when choosing which approach is most suitable for patients undergoing TAVR for severe aortic stenosis.